Precision soft tissue balancing: grid-assisted pie-crusting in total knee arthroplasty - Rezaei, Arash; Moon, John; Lichtig, Asher; Mera, Barbara; Drake, Brett; Choubey, Apurva S.; Kim, Sunjung; Tueni, Nicole; Piponov, Hristo; Koh, Jason; Karam, Joseph; Amirouche, Farid (Frontiers in Surgery, 2024)
Introduction The varus and valgus knee deformities result from imbalance in tension between medial and lateral soft tissue compartments. These conditions need to be addressed during total knee arthroplasty (TKA). However, there is no consensus on optimal soft-tissue release techniques for correcting varus and valgus deformities during TKA. We assessed the efficacy of a novel grid-based pie-crusting technique on soft-tissue release. Methods Cadaver knees were dissected, leaving only the femur and tibia connected by an isolated MCL or the femur and fibula connected by an isolated LCL. Bone cuts were made as performed during primary TKA. Mechanical testing was performed using an MTS machine. A 3D-printed 12-hole grid was placed directly over the MCL and LCL. Using an 18-gauge needle, horizontal in-out perforations were made 3 mm apart. Deformation and stiffness of the ligaments were collected after every 2 perforations. Means were calculated, and regression analyses were performed. Results A total of 7 MCL and 6 LCL knees were included in our analysis. The mean medial femorotibial (MFT) space increased from 6.018 ± 1.4 mm–7.078 ± 1.414 mm (R2 = 0.937) following 12 perforations. The mean MCL stiffness decreased from 32.15 N/mm–26.57 N/mm (R2 = 0.965). For the LCL group, the mean gap between the femur and ﬁbula increased from 4.287 mm–4.550 mm following 8 perforations. The mean LCL stiffness decreased from 29.955 N/mm–25.851 N/mm. LCL stiffness displayed a strong inverse relationship with the number of holes performed (R2 = 0.988). Discussion Our results suggest that using this novel grid for pie-crusting of the MCL and LCL allows for gradual lengthening of the ligaments without sacrificing their structural integrity. Our proposed technique may serve as a valuable piece in the soft-tissue release toolkit for orthopaedic surgeons performing TKA in varus and valgus deformed knees.